The Effect of Corn Silk (Zea Mays L) Extract Variation in Making Marshmallows on Chemical and Organoleptic Properties - Dini Dwi Anggaini; Haslina Haslina; Anisa Rachma Sari; Dewi Larasati; Yovita Aryani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Marshmallows are soft, chewy candies characterized by their light, foamy texture. They are typically formulated with gelling agents like gelatin, pectin, or starch, and have a water content of 12-20%. Their composition primarily includes sucrose and liquid glucose, resulting in a mildly sweet taste. This study explores enhancing marshmallows’ nutritional value by incorporating corn silk extract, an inexpensive and abundant corn by-product that is often underutilised. Corn silk is rich in antioxidants and possesses a subtle aroma and flavor, making it an ideal natural additive. This research aimed to evaluate the impact of corn silk extracts on the chemical and organoleptic properties of marshmallows and identify the selected formulation. Using a completely randomized design (CRD) with five concentrations of corn silk extracts (P1: 10%, P2: 20%, P3: 30%, P4: 40%, and P5: 50%) and four repetitions. The study analyzed water, ash, sucrose content, pH, and organoleptic properties (color, texture, and taste). Results indicated that adding corn silk extracts significantly (P<0.05) affected all tested parameters. The selected formulation was P1 (10% corn silk extracts). This formulation yielded marshmallows with a water at 16.18%, an ash at 0.91%, a sucrose content at 31.78%, and a pH at 6.80. Organoleptically, P1 marshmallows scored highly for color (6.32, very much like-very much like), texture (5.32, like-very much like), and taste (5.20, like-very much like). Corn silk extracts potential to enhance marshmallow characteristics and provide an innovative use for this agricultural byproduct. Contribution to Sustainable Development Goals (SDGs):SDG 6: Promotes sustainable use of agricultural resources to reduce environmental pollution affecting water quality.SDG 11: Supports sustainable communities through value-added utilization of agricultural by-products.SDG 13: Helps reduce agricultural waste and supports climate-friendly food production.SDG 15: Encourages sustainable land resource management through the utilization of corn silk waste.